10 NEWVARIABLE STARS IN THE CONSTELLATION ANTLIA - Sergey, Ivan; Dubrouski, Sergei; Baluk, Igor; Pobyiaha, Alexander (Одеські астрономічні публікації, 2014)
10 new variable stars in the constellation Antlia are reported, their phenomenological characteristics are listed.